ANALYSIS OF LOAN DISBURSEMENT AT PT LAMPUNG BERKAH FINANSIAL TEKNOLOGI - Putu Intan Puspita Sari; Luke Suciyati Amna; Riswan Riswan (Transpublika Publisher, 2024)
This study investigates the advancements in digital technology and the role of fintech, particularly in the realm of peer-to-peer lending. It specifically focuses on the challenges faced by start-up companies like Lahan Sikam in areas with diverse social structures. The potential risk of default poses a significant threat to consumer confidence. The background section provides an overview of the fintech industry's current state, highlights the challenges faced by Lahan Sikam as a start-up, and establishes objectives to comprehend the company's profile and its funding products. A qualitative research approach with a descriptive methodology was employed at PT Lampung Berkah Finansial Teknologi, where internal control and the application of the 5C principles in credit risk management were observed. Through interviews and observations, the implementation of these principles was revealed. The findings demonstrate that Lahan Sikam has effectively incorporated the 5C principles in assessing borrower risk, focusing on character, capacity, capital, collateral, and conditions.